AN ANALYSIS OF SLANG LANGUAGE IN SONG LYRICS USED BY “AVRIL LAVIGNE” - saputri, wulan sari (Journal of English Language Teaching and Literature (JELTL), 2021)
The objective of this study are to find out slang language in song lyrics used by Avril Lavigne tofind out the meaning of the slang language in song lyrics used by Avril Lavigne. This study concernwith the analysis slang language in Avril Lavigne song lyrics. This study is descriptive qualitative.The data classified based on word formation processes according to Yule's theory (2010). In thedata analysis the writer applied qualitative. Method and focused on content analysis. The analysisstarted on January 2020 until July 2020. This final project based on a study which attemps to findslang language in Avril Lavigne Song lyrics, and know the types slang language used in AvrilLavigne song lyrics. The results of study, the slang language words of the song Avril Lavigne alsoinfluenced by some of word formation, there are twelve type of slang word formation. There areCoinage, Compounding, Clipping, Blending, Borrowing, Back formation, Acronyms, Multipleprocess, Affixes (Prefix, Infix, Suffix). There are four types of slang language were identified basedon the findings used in Avril Lavigne song lyrics found 4 clipping, 10 blending, 2 compounding,and 1 Back formation . Based on the research, the process of blending is the most common processthat is found in Avril Lavigne song.